Examining The Influence Of Support Factors On The Performance Of Sustainable Agriculture Practices (International Journal of Food and Nutritional Sciences, 2022)
Farmers attitude towards the agricultural practices have been changing towards the organic farming or sustainable agriculture in India for the past one decade. The agricultural sector needs innovative technologies to make shift from production oriented farming to profit oriented sustainable farming. Farmers are also now realizing the significance of the sustainable agriculture practices both from the economic and ecological point of view. But they need various aspects of supports for the effective and efficient performance. Though, many farmers started practising sustainable agriculture practices for more than a decade, but still the exact performance of the sustainable practices over the years has not yet been studies extensively. The performance of the farmers in sustainable agricultural practise to be studied in order to evaluate the further improvements and future scope of sustainable agriculture practices. The purpose of this study was to examine the influence of various aspects of support like subjective norms, government support, supply chain support, society support etc., on the performance of sustainable agriculture practices of farmers. The respondents of this study consisted of 293 farmers of Coimbatore district in Tamil Nadu, India. A structured questionnaire was used to collect the data. Regression analysis was carried out to study influence of support factors on performance. The findings of this study showed that there is a significant positive influence of various aspects of attitude of the support on the performance of the farmers in sustainable agricultural practise. Based on the findings, managerial implications and future scope for the study have been suggested to the concerned stake holders.